High Fidelity Scan Merging - Digne, J.; Morel, J.-M.; Audfray, N.; Lartigue, C. (Computer graphics forum, 2010)
For each scanned object 3D triangulation laser scanners deliver multiple sweeps corresponding to multiple laser motions and orientations. The problem of aligning these scans has been well solved by using rigid and, more recently, non‐rigid transformations. Nevertheless, there are always residual local offsets between scans which forbid a direct merging of the scans, and force to some preliminary smoothing. Indeed, the tiling and aliasing effects due to the tiniest normal displacements of the scans can be dramatic. This paper proposes a general method to tackle this problem. The algorithm decomposes each scan into its high and low frequency components and fuses the low frequencies while keeping intact the high frequency content. It produces a mesh with the highest attainable resolution, having for vertices all raw data points of all scans. This exhaustive fusion of scans maintains the finest texture details. The method is illustrated on several high resolution scans of archeological objects.